Development attendance system with fingerprint reader - Nurul Afifah Bt. Abdul Kadir (School of Microelectronics, University Malaysia Perlis, 2015)
This project will provides hands-on experience in interfacing fingerprint reader with PIC microcontroller through UART (Universal Asynchronous Receiver / Transmitter). On the other hand, UNISA1 also include an extra programmed UART port to interface with PC computer .In order for UNISA1 to export attendance list to personal computer, I need to develop a Fingerprint Reader GUI using Microsoft Visual Studio 2010. Fingerprint Reader GUI not only retrieves the attendance list yet it can directly interface with SNFPR-UART fingerprint reader to perform some commonly used operations. Fingerprint Reader GUI interface with UNISA1 board and also SN-FPR-UART fingerprint reader through COM port. Attendance view is display in LCD screen after student identification. But an error occur when export attendance list from reader to GUI/Hyper terminal window because the setup of connection of transceiver and receiver of MAX232 through personal computer and UNISA1 is not correct. Also the Microsoft Visual Studio is not correctly program for GUI.